Kinetika Adsorpsi Logam Timbal (Pb) Menggunakan Ampas Tebu dan Gambas Kering pada Air Sumur Gali Sekitar TPA Batu Layang - Agustin, Dela Tri; Apriani, Isna; Winardi, Winardi (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The dug well water around Batu Layang landfill contains heavy metals, namely lead (Pb) and iron (Fe). This study aims to determine the adsorption kinetics model of each activated carbon. Heavy metal sorption uses activated carbon made from bagasse (AT), dried gambas (GK), and a combination (ATGK). The research method used jar tests with mass variations of 1 g, 2 g, 3 g and contact times of 30 and 60 minutes. Activation of activated carbon using 0.5 M HCl solution for 24 hours. Kinetics analysis is based on first-order and second-order kinetics. Langmuir, Freundlich, and BET adsorption equations are used in the adsorption process. The results showed that the adsorption kinetics of Pb metal for AT and GK activated carbons followed the second order while ATGK followed the first order. The adsorption equation for Pb metal for AT and GK activated carbon follows the Freundlich isotherm and ATGK activated carbon follows the BET isotherm. This research is important to see the potential of activated carbon made from AT and GK to be effective in adsorbing heavy metals.